Single event latch-up detection for nano-satellite external solar radiation mitigation system - Norsuzila Yaa’cob; Muhammad Fauzan Ayob; Noraisyah Tajudin; Murizah Kassim; Azita Laily Yusof (Institute of Advanced Engineering and Science, 2021)
This paper presents the single event latch-up (SEL) detection for nano-satellite external solar radiation mitigation system. In this study, the SEL detection analysis was conducted using circuit test and simulation. An electrical power subsystem (EPS) is a part of all CubeSat bus subsystems and it comprises solar arrays, rechargeable batteries, and a power control and distribution unit (PCDU). In order to extract the maximum power generated by the solar arrays, a peak power tracking topology is required. This may lead to the SEL with the presence of high voltage produced by solar. To overcome the SEL problems, the circuit test and simulation must be done so that the flow of SEL will be easily detected and mitigate. The method that been used are by using microcontroller, the SEL will be created in the certain time. The programable integrated circuit (PIC) are used to mitigate SEL effect. It indicates that, the SEL occur very fast in certain time. When the simulation is conducted by using SPENVIS, the result shows, only single event upset (SEU) was affected on UiTMSAT-1.